Chemical activation of commodity plastics for patterned electroless deposition of robust metallic films. Issue 74 (30th August 2022) - Wagner, Jessica R.; Fletcher, Jared; Morin, Stephen A.
Abstract : A metal-chelating polymer (PEI) was used to modify the surface of commodity plastics, yielding a generalizable procedure for producing strongly adhered metallic traces using electroless deposition. Abstract : A general approach to increase the adhesion of metal films to commodity plastic substrates using a metal-chelating polymer, polyethyleneimine, in conjunction with patterned electroless deposition is described. This general fabrication method is compatible with a diverse array of plastics and metals with properties applicable to flexible electronic circuits and electrochemical cells.